The Effect of Financial Literacy, System Security, and Accounting Information System Quality on Transaction Effectiveness in Mobile Banking Usage - Candra Prihatini; Rina Destiana (Rescollacom (Research Collaborations Community), 2026)
The development of Mobile Banking services requires reliable information systems to support the effectiveness of digital financial transactions. This study aims to analyze the effects of financial literacy, system security, and accounting information system quality on the effectiveness of Mobile Banking transactions. This research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to Mobile Banking users. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that, partially, financial literacy and system security do not have a significant effect on the effectiveness of Mobile Banking transactions. In contrast, the quality of the accounting information system has a positive and significant effect on transaction effectiveness and emerges as the most dominant variable. Simultaneously, financial literacy, system security, and accounting information system quality have a significant effect on the effectiveness of Mobile Banking transactions, with a coefficient of determination of 67.1%. These findings emphasize that the quality of accounting information systems plays a crucial role in enhancing the effectiveness of Mobile Banking transactions; therefore, banks need to prioritize the development of system quality to improve digital service performance.